Multiwavelength study of the G345.5+1.5 region - Figueira, M. (2019)
Context. The star formation process requires the dust and gas present in the Milky Way to self-assemble into dense reservoirs ofneutral material where the new generation of stars will emerge. Star-forming regions are usually studied in the context of Galacticsurveys, but dedicated observations are sometimes needed when the study reaches beyond the survey area.Aims. A better understanding of the star formation process in the Galaxy can be obtained by studying several regions. This allowsincreasing the sample of objects (clumps, cores, and stars) for further statistical works and deeper follow-up studies. Here, we studiedthe G345.5+1.5 region, which is located slightly above the Galactic plane, to understand its star formation properties.Methods. We combined the Large Apex BOlometer CAmera (LABOCA) and 12 CO(4−3) transition line (NANTEN2) observationscomplemented with the Hi-GAL and Spitzer-GLIMPSE surveys to study the star formation toward this region. We used the Clumpfindalgorithm to extract the clumps from the 870 μm and 12 CO(4−3) data. Radio emission at 36 cm was used to estimate the number ofH ii regions and to remove the contamination from the free-free emission at 870 μm. We employed color-color diagrams and spectralenergy distribution (SED) slopes to distinguish between prestellar and protostellar clumps. We studied the boundedness of the clumpsthrough the virial parameter. Finally, we estimated the star formation efficiency (SFE) and star formation rate (SFR) of the region andused the Schmidt-Kennicutt diagram to compare its ability to form stars with other regions of the Galactic plane.Results. Of the 13 radio sources that we found using the MGPS-2 catalog, 7 are found to be associated with H ii regions correspondingto late-B or early-O stars. We found 45 870 μm clumps with diameters between 0.4 and 1.2 pc and masses between 43 M and3923 M , and 107 12 CO clumps with diameters between 0.4 pc and 1.3 pc and masses between 28 M and 9433 M . More than 50%of the clumps are protostellar and bounded and are able to host (massive) star formation. High SFR and SFR density (ΣS FR ) valuesare associated with the region, with an SFE of a few percent.Conclusions. With submillimeter, CO transition, and short-wavelength infrared observations, our study reveals a population of mas-sive stars, protostellar and bound starless clumps, toward G345.5+1.5. This region is therefore actively forming stars, and its locationin the starburst quadrant of the Schmidt-Kennicutt diagram is comparable to other star-forming regions found within the Galacticplane.